Breeding observations of the Black-winged Kite Elanus caeruleus (Desfontaines, 1789) in Iraq. Issue 1 (2nd January 2018) - Abed, Salwan Ali; Salim, Mudhafar A.
Abstract: This study was conducted in order to examine the breeding occurrence of the Black-winged Kite Elanus caeruleus at several locations in Al-Qadisiyah Province of the Middle Euphrates region, Iraq, in 2017. Three active nests were regularly observed from April through July 2017. All three nests were located in date palms Phoenix dactylifera, close to the center of the tree, at the average height of 7.73 m above the ground. The clutch size of four eggs and the 100% hatching success were recorded for all the three nests. The mean fledging success reached 92% for the three nests. The current study contributes to the knowledge of the global breeding distribution of the Black-winged Kite and sheds some light on the breeding ecology of the species in Iraq.